PENGATURAN PEMANFAATAN PERDAGANGAN JENIS IKAN DILINDUNGI/APPENDIKS CITES DI WILAYAH KERJA LPSPL SERANG - Suko Wardono; Syarif Iwan Taruna Alkadrie; Arief Surya Wibowo; Ayuningtyas Sekarputri Reksajaya; Wibowo Wibowo; Gusti Aries (Jurnal Teknologi Perikanan dan Kelautan, 2022)
The Convention on International Trade in Endangered Species (CITES) of Wild Fauna and Flora which has been ratified through Presidential Decree No. 43 of 1978, is the nation's commitment to the conservation of endangered, endemic, and protected fish species. Trading traffic of protected fish species/CITES Appendix in of the Coastal Resources Management Regional Office (LPSPL) Serang working area is quite high, so it is necessary to control the utilization of protected fish species to maintain the sustainability of fish resources. The method of collecting data is through recording and direct interviews with service officers and treasurers of LPSPL Serang, as well as secondary data from service databases on traffic activities for protected fish species/CITES Appendix during Semester I (January-June) year 2022. Based on data collected, 53 domestic recommendation letters have been issued consisting of 30,909.80 kg of shark products, 104.50 kg of ray fins, 1,308 kg of sea cucumbers, and 12,009 pcs of soft coral and anemone; Foreign recommendation letters totaling 1,317 recommendations consisting of 2,335,464.01 kg of shark products and 283 live sharks, 468,387.55 kg of ray products and 21 live rays, 24,121.86 kg of sea cucumbers, and 295,408 pcs of soft coral and anemone; Documents for transport of fish species consisting of 28 documents consisting of 53,595 arowanas and 3,752.79 kg of shark and ray fins in the CITES Appendix; Letters of transport for tentengan fish types consisting of 228 documents of 359 arowanas. Total value of PNBP obtained is Rp 1,312,204,811.